Genetic Analysis of Cone and Seed Characters of Plus Trees of Deodar (cedrus Deodara (roxb.) G.don) - Sharma, Rajesh (Indian Forester, 2014)
Cones were collected during 2006 from fifty two plus trees of deodar (Cedrus deodara) selected in the state of Himachal Pradesh from the stands of site quality II/III with average ageof 80-100 years and of 50-60 cm diameter class. Significant differences (p=0.05) were observed among plus trees for cone length, cone diameter, cone weight, number of seed, seed length, seed width and seed weight indicating that a significant amount of genetic variation exists among plus trees for these traits. Wide ranges in the means were exhibited for cone diameter (4.60-8.0 cm), cone weight (82-302.80 g), number of seed (120- 230) and seed weight (8.86-16.35 g). In all cases the standard error was lower than their respective means. Of the 28 correlations, cone diameter and cone weight (0.39), seed length and seed width (0.48), seed length and seed weight (0.62) and seed width and seed weight (0.58) were found to have positive and highly significant genetic correlation. Cone weight, which recorded highest estimate of heritability (98.88%), also recorded highest genetic gain of 67.56 %.